PERANCANGAN ULANG UI/UX WEBSITE SDIT NURUL ILMI BILIGUAL INTEGRATED SCHOOL BEKASI MENGGUNAKAN METODE DESIGN THINKING - Andreas Eka Pradana; Ika Kurniawati; Fachri Amsury; Heriyanto Heriyanto (Universitas Majalengka, 2024)
ABSTRACT SDIT Nurul Ilmi Bilingual School Integrated Bekasi is one of the educational institutions that utilizes the advancement of technology and the internet that is currently growing by providing a school website that contains several features such as online new student admissions and e-reports along with other information. The lack of information available regarding new student admissions, academic information, and school programs available on the school website owned by SDIT Nurul Ilmi Bilingual School Integrated Bekasi makes users dissatisfied in using the website. The redesign of this website uses the design thinking method which is a human-centered design approach to understand user needs and problems and create new innovations. The results of the prototype testing using Maze as a whole were 96%, which means that the prototype design that was tested can work well and is easy to understand by users. The results of usability testing on the prototype obtained an average score of 88 which showed excellent results with a grade scale of B, which means that the system is declared feasible. The results of the redesign in the form of a prototype can be used by related parties, namely website developers. Keywords: User interface, User Experience, Design Thinking Abstrak SDIT Nurul Ilmi Bilingual School Integrated Bekasi merupakan salah satu lembaga pendidikan yang memanfaatkan kemajuan teknologi dan internet yang semakin berkembang saat ini dengan menyediakan website sekolah yang di dalamnya terdapat beberapa fitur seperti penerimaan siswa baru secara online dan e-raport beserta informasi-informasi lainnya. Minimnya informasi yang tersedia mengenai penerimaan siswa baru, informasi akademik, dan program sekolah yang tersedia pada website sekolah yang dimiliki SDIT Nurul Ilmi Bilingual School Integrated Bekasi membuat user belum puas dalam menggunakan website tersebut. Perancangan ulang webstite ini menggunakan metode design thinking yang merupakan pendekatan desain berpusat pada manusia untuk memahami kebutuhan dan masalah pengguna serta menciptakan inovasi baru. Hasil testing prototype menggunakan Maze secara keseluruhan sebesar 96% yang artinya desain prototype yang diuji dapat bekerja dengan baik dan mudah dipahami oleh pengguna. Hasil usability testing pada prototype memperoleh nilai rata-rata 88 yang menunjukan hasil excellent dengan grade scale B yang artinya sistem dinyatakan layak. Hasil re-design yang berupa prototype ini dapat digunakan pihak terkait yakni pengembang website. Kata Kunci: User interface, User Experience, Design Thinking